Assessment of strategic healthcare purchasing and financial autonomy in Tanzania: the case of results-based financing and health basket fund - Maiba, John; Singh, Neha S.; Cassidy, Rachel; Mtei, Gemini; Borghi, Josephine; Kapologwe, Ntuli A.; Binyaruka, Peter (Frontiers in Public Health, 2024)
Background: Low-and middle-income countries (LMICs) are implementing health financing reforms toward Universal Health Coverage (UHC). In Tanzania direct health facility financing of health basket funds (DHFF-HBF) scheme was introduced in 2017/18, while the results-based financing (RBF) scheme was introduced in 2016. The DHFF-HBF involves a direct transfer of pooled donor funds (Health Basket Funds, HBF) from the central government to public primary healthcare-PHC (including a few selected nonpublic PHC with a service agreement) facilities bank accounts, while the RBF involves paying providers based on pre-defined performance indicators or targets in PHC. We consider whether these two reforms align with strategic healthcare purchasing principles by describing and comparing their purchasing arrangements and associated financial autonomy.We used document review and qualitative methods. Key policy documents and articles related to strategic purchasing and financial autonomy were reviewed. Indepth interviews were conducted with health managers and providers (n=31) from 25 public PHC facilities, health managers (n=4) in the Mwanza region (implementing DHFF-HBF and RBF), and national-level stakeholders (n=2). In this paper, we describe and compare DHFF-HBF and RBF in terms of four functions of strategic purchasing (benefit specification, contracting, payment method, and performance monitoring), but also compare the degree of purchaser-provider split and financial autonomy. Interviews were recorded, transcribed verbatim, and analyzed using a thematic framework approach.